Media policy in Greenland - Ravn-Højgaard Signe (Nordicom Review)
This article describes the historical development of media policy in Greenland, and the shifts in the underlying normative and causal ideas that legitimise media policy. I argue that media policy reflects changes in Greenland's political system. Specifically, under colonial rule, Greenlandic media was state run and media was seen as an instrument to educate the population. Gradually, with the introduction of home rule, a paradigm shift took place, whereby media was seen as a vital instrument to strengthen Greenlandic language and identity. At the same time, normative ideas of media independence appeared which called for institutionalisation of the arm's length principle. Due to the influence and institutional spill-over from Denmark, I argue, Greenlandic media policy fit rather well into the “Nordic media model” although media policy in Greenland is mostly formulated without long-term or broad political agreements.